Cytokinin Response of the Streptophyte Alga Coleochaete scutata provides a clue to the evolution of cytokinin signaling - Pinto, Sandra; Tajeshwar, Navindra; Gordon, Kyana; Borrero, Paloma; Novák, Ondřej; Strnad, Miroslav; Foellmer, Matthias; Heyl, Alexander (Frontiers in Plant Physiology, 2023)
Introduction Cytokinins, a group of adenine derivatives, are phytohormones that regulate many aspects of the plant's reaction to changes in the abiotic and biotic environment and ensure the correct execution of developmental programs. While the signaling pathway and its effects are very well established for Angiosperms, its origin, and evolution are less well understood. Methods The first step in the analysis of the cytokinin signaling pathway is to test if the organism can react to the hormone. Thus, an assay was established, that uses differences in the growth pattern of the Streptophyte alga, Coleochaete scutata, to determine if this algal species reacts to different cytokinins. Results Surprisingly not only classical cytokinins, such as trans-zeatin and kinetin, led to a change in the pattern of growth, but also adenine, which is usually used as a negative control. Discussion This raises questions about the origin and the functioning of the cytokinin signaling in C. scutata and also in algae in general.